High resolution magnetic resonance imaging for exposing facial nerve zonal vulnerability to microbleeds: A rare cause of facial palsy. Issue 4 (August 2017) - Hsu, Charlie Chia-Tsong; Singh, Dalveer; Watkins, Trevor William; Kwan, Gigi Nga Chi; Hapugoda, Sachintha
Background: We report a case of hypertensive microbleeds strategically located at the attached segment (AS) and root entry zone (REZ) at the left facial nerve causing facial paralysis. Case Report: A 60-year-old woman presented with sudden onset left facial paralysis. Medical history was significant for poorly controlled hypertension secondary to bilateral adrenal hyperplasia (primary hyperaldosteronism). The patient was initially treated for presumptive Bell's palsy. Subsequent magnetic resonance imaging of the brain and internal auditory canal showed two microbleeds at the left cerebellopontine angle. Dedicated coronal T1 magnetization prepared rapid acquisition gradient echo and T2 sampling perfection with application optimized contrasts using different flip angle evolution sequences revealed two acute microbleeds located at the attached AS and REZ of the left facial nerve. The patient experienced only partial recovery from House–Brackmann grade IV facial paralysis at presentation to a House–Brackmann grade III facial paralysis at 1 year of follow up. Conclusions: To the best of the authors' knowledge, this is the first reported case of facial paralysis caused by microbleeds directly affecting the vulnerable AS and REZ facial nerve segments. We discuss the zonal microanatomy of the facial nerve and the crucial role of high resolution MRI for diagnosis.